Case report: Changes in defense mechanisms, personality functioning, and body mass index during psychotherapy with patients with anorexia nervosa - Conversano, Ciro; Di Giuseppe, Mariagrazia; Lingiardi, Vittorio (Frontiers in Psychology, 2023)
Eating disorders (EDs) are difficult to treat in psychotherapy due to their pervasive symptomatology and frequent and rapid relapses. Restrictive anorexia nervosa (AN) is the most challenging ED, often associated with severe physical and mental conditions. Perceived as an ego-syntonic syndrome that somehow protects the patient from a number of developmental tasks, treating AN requires extensive multidisciplinary long-term intervention. As with other emotion regulation strategies, defense mechanisms mediate an individual's reaction to internal or external stressors, including those related to ED conditions. Improving defensive functioning adaptiveness predicts psychotherapy outcomes and is an essential component of the therapeutic process. In this study, we qualitatively described changes in the use of defense mechanisms, personality functioning (PF), and body mass index (BMI) in two patients with severe AN in treatment with intense dynamic psychotherapy. Changes in personality functioning and defense mechanisms were periodically assessed every 6 months using clinician report measures such as the Shedler-Westen Assessment Procedure-200 (SWAP-200) and the Defense Mechanisms Rating Scales Q-sort (DMRS-Q), respectively. BMI was also monitored throughout the treatment. A qualitative description of the patient's defensive profile and the quantitative score on all ranges of defense mechanisms were used for studying changes in patients' use of defenses during the treatment and relationships between defenses and outcome indexes. Personality and defensive functioning improved after 1 year of intense dynamic psychotherapy, independently from BMI improvement. All outcome indexes dramatically decreased before a scheduled interruption of the treatment, underling that an integrated therapeutic approach is essential for improving and eventually orienting toward complete ED symptoms remission. Long-term dynamic psychotherapy fosters self-awareness of psychological distress and enhances more mature ways of coping. Monitoring changes in personality and defense mechanisms helps in understanding patients' reactions to stressful life events and in developing specific therapeutic interventions.